Consequences of amniocentesis and chorionic villus sampling for prenatal diagnosis - Cederholm, Maria (Uppsala universitet, Institutionen för kvinnors och barns hälsa, 2002)
Amniocentesis (AC) and chorionic villus sampling (CVS) are the principal methods for fetal karyotyping. The aim of this thesis was to evaluate psychological reactions and risks associated with the procedures. A semi-randomised study was made on 321 women, where AC (147) and CVS (174) at 10-13 weeks’ gestation were done trans-abdominally. Spontaneous fetal loss occurred in 6.8% and 1.7% of the women in the AC and CVS groups, respectively. Repeat testing was required more often in the AC (19.0%) than in the CVS (5.2%) group. A subgroup of 94 women answered a questionnaire prior to the procedure. Anxiety was stated as reason for invasive testing in 38% of the women. Mean scores according to the Hospital Anxiety and Depression Scale for anxiety and depression were low. Likewise, mean scores for the Impact of Event Scale, evaluating the psychological distress evoked by the procedure, were low. Yet, a number of women had higher scores, indicating a risk of clinical anxiety and depression or psychological distress. The women worried most about miscarriage, fetal injury by the procedure and waiting for the result. Fetal, infant and maternal outcomes were evaluated in a cohort of 71 586 women aged 35 to 49 years old, with single births in Sweden during 1991 to 1996. Altogether, 21 748 were exposed to AC and 1984 to CVS. Women exposed to AC and CVS were compared with non-exposed. Outcomes were extracted from the Swedish Medical Birth Register, the Swedish Hospital Discharge Register, and the Swedish Malformation Register. An increased risk of musculo-skeletal deformities, such as club foot (OR=1.45) and hip dislocation (OR=1.22), and respiratory disturbances such as neonatal pneumonia (OR=1.29), was found for infants born in the AC group. Risk increased with earlier gestation at the procedure. Fewer women in the AC group had a normal delivery and more had a Caesarean section. Complications related to the amniotic cavity and membranes (OR=1.15), hypotonic uterine dysfunction (OR=1.12) and instrumental vaginal deliveries (OR=1.11) were more common in the AC group. No significant differences were found for the CVS group. CVS is the method of choice for prenatal karyotyping in the first trimester. AC should not be performed before 15 weeks’ gestation. Further research to develop methods to better identify women at increased risk of chromosomal abnormal pregnancies and to develop non-invasive tests for prenatal diagnosis is needed. Thereby, the number of women exposed to invasive procedures and the adverse effects caused by these procedures can be minimised.